Myo-inositol: therapeutic possibilities and pregravid preparation in women with pcos - Л. В. Калугина; Т. И. Юско (Publishing House TRILIST, 2018)
Polycystic ovary syndrome (PCOS) as one of the main causes of ovarian dysfunction in women of reproductive age accounts for more than half of infertility cases of endocrine origin (50-75%), and increases the risk of miscarriage and such perinatal complications as gestational diabetes, fetal macrosomia, gestational hypertension (preclamation, pregnancy-induced hypertension). Due to metabolic, hormonal disorders, patients with PCOS have an increased risk of anovulatory cycles and constitute the main group of women who resort to the IVF procedure, they also have a 10-fold increased risk of type 2 diabetes and cardiovascular disease, as well as cancer endometrium and breast cancer. The search for pharmacological substances for pathogenetic therapy of PCOS continues, whereas modern approaches to treatment are mainly aimed at correcting insulin resistance, restoring the menstrual cycle, ovulating, reducing the manifestations of hyperandrogenism, and presenting symptomatic therapy. It is on the correction of metabolic disorders sent recommendations for lifestyle modification, which provide for rational nutrition, metered physical exertion, as well as an additional intake of vitamin-mineral complexes, since PCOS is a neuroendocrinal syndrome that requires constant maintenance therapy. A systematic analysis of the studies conducted in this study showed that the inclusion of myo-inositol in a 4 g per day to treatment of PCOS reduces the insulin resistance, excessive androgen secretion, the risk of hirsutism and acne, the normalization of the lipid profile and the restoration of fertility. The data obtained make it possible to include myo-inositol in pregravid preparation of patients with PCOS, as well as in the preparations for the IVF procedure, than to significantly improve its result in patients with PCOS and other pathologies associated with infertility. As a myo-inositol-containing preparation for the pregravid preparation of women with PCOS, an innovative complex can be recommend: myo-inositol + 5-methyltetrahydrofolate + vitamin B12, which necessary for the prevention of neural tube defects, hyperhomocysteinemia and miscarriage.